Jurisprudence Study of the Importance of the Role of a Woman’s Right to Have a Child: A Review - Ghodrati, Fatemeh (Current Women's Health Reviews, 2020)
Background: Every woman has the right to have children. Objective: This study aimed to investigate the Jurisprudence study of the importance of the role of a woman right to have a child. Methods: A review of the literature with keywords of motherhood. The viewpoints of the jurists, jurisprudent law, right contraception and breastfeeding, spiritual rewards, pregnant women, instinct of having a child and the Quran. The Information Centers such as Scopus and Iranmedex, Magi ran SID, Google Scholar, Science Direct, Pub med, and in the returns without any time limitations up to 2018. Therefore, Qur'anic verses based on the topic and authentic Hadith texts as well as authoritative, authentic scientific articles. Results: Narrations and Quran verses on greatness and respect of a mother show the importance of the maternal role. The maternal role is a fabulous facet of perfection of a woman and Islam has considered spiritual rewards for it. In the Quran, many biological changes such as pregnancy, childbirth, breastfeeding and taking care of a child and spiritual characteristics of mothers as the instinct seeking a child or generosity towards child have been mentioned. Islamic rules have a duty to extend this culture and aid mothers to achieve this right. Nobody can deprive a woman of it. Conclusion: In view of jurisprudent rules in Islam, if there is no limitation or natural barrier for a woman to have a child but her husband’s illogical unwillingness for having a child; this is, according to article 1130 of civil law, a kind of distress and embarrassment and the woman has the right to divorce.
Keywords: jurisprudent